Doctrine of implied powers as a judicial tool to build federal polities : comparative study on the doctrine of implied powers in the European Union and the United States of America - Hodun, Milosz Marek, 1984- (2015)
Doktorsritgerð frá lagadeild Háskólans í Reykjavík.